Tractates Ševu'ot and 'Avodah Zarah - Guggenheimer, Heinrich W. (Studia Judaica, 2011)
This is volume 13 of the edition of the complete Jerusalem Talmud. Within the Fourth Order Neziqin ("damages"), these two tractates deal with various types of oaths and their consequences (Ševu'ot) and laws pertaining to Jews living amongst gentiles, including regulations about the interaction between Jews and "idolators" ('Avodah Zarah).